Destruction of Surface-Inoculated Escherichia coli, Vibrio cholerae and Salmonella typhi in Rohu (Labeo rohita) Steaks during Microwave Cooking - A.U., Muzaddadi; B.B., Nayak (Fishery Technology, 2025)
The destruction of bacteria during microwave cooking of fish was studied. Fish steaks were surface-inoculated with Escherichia coli, Vibrio cholerae and Salmonella typhi and cooked in a microwave oven. The bacteria were enumerated by plating on selective and non selective media and by MPN technique. The vegetative cells of S. typhi and V. cholerae were totally destroyed from an initial count of 107 cfu/g to a non detectable level and E. coli was destroyed from an initial count of 107 cfu/g to 1 cfu/lOg after microwave treatment. Cooking for a longer duration at low power output level was found to ensure the killing of pathogens and minimize bumping without any distortion of shape.